PENENTUAN STATUS MUTU AIR TUKAD YEH POH DENGAN METODE STORET - Kadek Ari Esta; Putu Suarya; Ni G. A. M. Dwi Adhi Suastuti (Jurnal Kimia (Journal of Chemistry), 2016)
This paper reports the examination of Tukad Yeh Poh river in terms of several parameters namely temperature, total suspended solids (TSS), electric conductivity, pH, dissolve oxygen demand (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), phosphate, Pb, Cu, fecal coliform and total coliform. Water sampling was done at three sampling stations, namely the upstream, midstream and downstream. The results of the water sample measurements were compared to the environmental quality standards and standard criteria of environmental damage by Bali Governor Regulation No. 8 in 2007. The results showed the presence of some parameters whose values exceeded the threshold of class II water quality standard. Those parameters were TSS, BOD, COD, phosphate, Pb, and Cu. The STORET assessment results of Tukad Yeh Poh upstream has a total score of -27 that was categorized as being polluted, while in the middle and downstream, -37 and -49 respectively, which were categorized as heavily polluted.